Degree of Burn: A Digital Tool for Burn Area Assessment and Fluid Requirement Calculation Using Wound Image Analysis - Agustin, Wahyu Rima; Rahmad, Muhamad Nur; Tobi, Hermiana Ernastin (PT Inovasi Pratama Internasional, 2025)
Burns are tissue damage due to contact with a heat source, such as fire, hot water, chemicals, electricity, or radiation. Burns are a type of trauma with high morbidity and mortality rates and require high treatment costs. In Indonesia, burns are still a serious problem that requires special care, high costs, and skilled personnel. Currently, burn assessments are carried out manually, which is time-consuming and the results are subjective. Treatment efforts include preventing infection and encouraging epithelial cell regeneration to close the wound. Therefore, innovation is needed in the form of a system that helps assess burns more effectively, including classifying wound tissue, measuring wound area, and monitoring wound development. The use of an Android-based system can provide more accurate measurements through a digital planimetry approach or image segmentation, which can identify wound boundaries and tissue types. Technology-based health applications, such as the